Integrasi Kearifan Lokal Rumah Panggung Melayu Dalam Pembelajaran Bangun Ruang di Sekolah Dasar - Mailani, Elvi; Nur Rarastika; Hanna Olyvia Manurung; Renni Lumban Gaol; Irma Ida Sihombing; Selviona Dara Perbina (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study examines the integration of Malay stilt houses as local wisdom in elementary school mathematics learning, especially in spatial geometry material. This study uses a descriptive qualitative method with a literature study approach, namely by examining various relevant literature sources to explore the potential for integrating local cultural values ​​into the context of mathematics learning. Malay house architecture contains geometric shapes such as blocks, pyramids, and prisms that are relevant to help students understand concepts concretely and meaningfully. This ethnomathematics approach also strengthens character, cultural identity, and supports the Pancasila Student Profile in the Merdeka Curriculum. Although its potential is great, its implementation still faces challenges such as limited teaching materials and teacher training. Therefore, it is necessary to develop local culture-based learning modules that are applicable in various regions